The Effect of Visual Learning Style and Problem Based Learning towards Mathematics Learning Outcomes Viewed from Emotional Intelligence - Prajitno, Sunyoto Hadi; Auliya, Alyarah Fardatul (Jurnal Pendidikan MIPA, 2022)
This study aims to determine whether there is an effect of visual learning style using the Problem Based Learning model on learning outcomes in terms of the emotional intelligence of class XI students of SMA Negeri 1 Menganti. The population used is class XI IPA and the selected sample is students of class XI IPA 2 and XI IPA 3 by applying the Problem Based Learning model. Data collection techniques used are questionnaires and student learning outcomes tests. From the results of the data analysis, the value of sig. (2-tailed) = 0.005 on the results of the visual learning style test with high emotional intelligence was obtained. Meanwhile, the visual style learning outcome test with moderate emotional intelligence obtained a value of sig. (2-tailed) = 0.000 and the visual learning style with emotional intelligence obtained a value of sig. (2-tailed) = 0.001. It can be said that there is an influence on visual learning style using Problem Based Learning on significant learning outcomes of the emotional intelligence of class XI students of SMA Negeri 1 Menganti in 2021/2022. Keywords: problem based learning, visual learning style, emotional intelligence, mathematics learning outcomes. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp392-399